P-wave electrocardiogram morphology in the differential diagnosis of supraventricular cardiac rhythm disorders - G. G. Ivanov; S. P. Leshchinsky; N. A. Bulanova (Сеченовский вестник)
Violations of the heart rhythm is nowadays one of the most current problems in cardiology. Violations of rhythm to a greater or lesser extent affect the hemodynamic condition from lack of circulation 1 degree up to fully stop circulatory system. Arrhythmia, which are described in this article, do not apply to life-threatening alarm condition is present, but can be the causes for study points out, lack of circulation and other pathological condition which treatment may be more difficult and longer than treatment of arrhythmia. Therefore, the timely and proper treatment of cardiac rhythm is the key lack of the patient's heavy and in individual cases, disabling complications. The key to proper treatment in turn is the correct diagnosis. Among survey methods which are necessary for a correct diagnosis one of the first places took a ECG. In this article the changes in morphology P-wave ECG that may contribute to differential diagnosis are evoked.